Viscosity-Coefficient and thermodynamics Parameter tor Viscosity Flow of Some Amino Acids During the Passage of Alternating Current at Different Voltages - Mansow, Saber E.; Hasieb, Ibrahtm H.; Abdul-kariem, Nadhim (Al-Mukhtar Journal of Sciences, 2009)
Knowledge of the individual contributions of all the protein constihrents is needed for’ a proper understanding of the significance of thermodynamic par’ameters for the denahrration of proteins in denaturant solutions. Thus, in this study the change in viscosity of some amino acids e.g. DL-alanine, L-prollne and L-vallne under the influence of symmetrical alternating current with applied voltages between zero and 250 volts at a frequencies 50Hz have been shrdied. The flow of symmetrical alternating current is found to decrease the viscosity of electrolyte solutions. This decrease may interpreated according to the change in solution structure and it is depend on the properties of solutions. The obtained results show that the values of (3- coefficient are positive and increase with increasing the numbei’ of cai’bon atoms in altyle chains in some amino acids at different voltagesKnowledge of the individual contributions of all the protein constihrents is needed for’ a proper understanding of the significance of thermodynamic par’ameters for the denahrration of proteins in denaturant solutions. Thus, in this study the change in viscosity of some amino acids e.g. DL-alanine, L-prollne and L-vallne under the influence of symmetrical alternating current with applied voltages between zero and 250 volts at a frequencies 50Hz have been shrdied. The flow of symmetrical alternating current is found to decrease the viscosity of electrolyte solutions. This decrease may interpreated according to the change in solution structure and it is depend on the properties of solutions. The obtained results show that the values of (3- coefficient are positive and increase with increasing the numbei’ of cai’bon atoms in altyle chains in some amino acids at different voltages